Bryophytes The State of Knowledge in a Changing World - Putzke, Jair (IntechOpen, 2023)
Bryophytes are tiny, fragile, photosynthetic plants found all over the world, from the poles to deserts and forest areas. They contribute one-third of the oxygen we breathe as well as remove harmful CO2 from the atmosphere, thus helping mitigate the effects of climate change. Fragile and silent in their micro-habitat, they do so much for the planet, yet very little is known about them. This book is the result of the effort of several authors who work with bryophytes. It includes six chapters that address such topics as diversity and taxonomy, ecology, and biochemistry. The chapters present data on various species of Bryophyta from different continents, including Peru, Indonesia, Brazil, and Argentina.